THE USE OF CUBING TECHNIQUE TO TEACH WRITING RECOUNT TEXT - Resi, Resi; Sudarsono, Sudarsono; Ikhsanudin, Ikhsanudin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aimed to exercise whether or not the use of cubing technique was significant to teach writing recount text to year-8 students of SMPN 8 Pontianak. This research was a pre-experimental study. The sample was Class VIII D students who consisted of 34 students. The data were collected from the pre-test and the post-test. The writing recount text test was used in this research to collect the data. Based on the data, the students’ mean score of pre-test was 38,02 and the students’ mean score of post-test was 66.1. It meant the score after administering the treatment was higher than before administering the treatment. Then, this research was analyzed by t-test which the t- value (13.1) was higher than the t-table (1.6909) in level 0.05.. The research finding was computed with effect size formula. The effect size was 2.24, higher than 0.8. It was qualified high. It meant that cubing technique is highly-effective to teach writing recount text. The cubing technique also eased students to develop and organize their ideas.Keywords: Cubing Technique, Technique, Teaching Writing, Recount Text.